2015
DOI: 10.1063/1.4916029
|View full text |Cite
|
Sign up to set email alerts
|

Spin wave spectra in perpendicularly magnetized permalloy rings

Abstract: The dynamic behavior of perpendicularly magnetized permalloy circular rings is systematically investigated as a function of film thickness using broadband field modulated ferromagnetic resonance spectroscopy. We observed the splitting of one spin wave mode into a family of dense resonance peaks for the rings, which is markedly different from the single mode observed for continuous films of the same thickness. As the excitation frequency is increased, the mode family observed for the rings gradually converges i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…[5,11,19] Although the ferromagnetic resonance (FMR) spectra of patterned films have been wisely researched, recent studies showed rich spin wave spectra of magnetic disks and rings at different magnetized states. [13,20,21] For example, when the magnetic field was applied in the film plane, the magnetic disks at remanence showed a magnetization transition from onion to vortex state depending on the magnitude of the applied field. [22][23][24] On the other hand, splitting of excitation spectra was observed if the magnetic rings magnetized along the direction of out-of-plane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5,11,19] Although the ferromagnetic resonance (FMR) spectra of patterned films have been wisely researched, recent studies showed rich spin wave spectra of magnetic disks and rings at different magnetized states. [13,20,21] For example, when the magnetic field was applied in the film plane, the magnetic disks at remanence showed a magnetization transition from onion to vortex state depending on the magnitude of the applied field. [22][23][24] On the other hand, splitting of excitation spectra was observed if the magnetic rings magnetized along the direction of out-of-plane.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] On the other hand, splitting of excitation spectra was observed if the magnetic rings magnetized along the direction of out-of-plane. [21] Furthermore, the resonance spectra of ring arrays are more complex than those of disks because of the unique topological structure of rings. In other words, disks are internally connected but rings are not.…”
Section: Introductionmentioning
confidence: 99%
“…This explains the extensive investigation of magnetic rings during the last twenty years. However, in previous studies of magnetic dynamics, the main attention was paid to thin rings (with thickness below 50 nm) [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Spin wave [1,2], defined as non-uniform precession of magnetic moment in a magnetic medium, has drawn significant attention in the last few decades [3]. Recently, the nano and submicron scale patterned magnetic films have drawn much attention due to being beneficial for understanding the spin configuration, spin wave excitation and quasi-static magnetization reversal mechanisms [4][5][6][7]. Due to the boundary condition, the static spin configurations vary because of the combination of internal field profiles and inter-element interaction, and then the quantized spin wave states can be excited in the microwave frequency region in these patterned magnetic films [8,9].…”
Section: Introductionmentioning
confidence: 99%